2019
DOI: 10.1128/jvi.01100-19
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus Induces Interleukin-17 Production via Activation of the IRAK1-PI3K-p38MAPK-C/EBPβ/CREB Pathways

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is widely prevalent in pigs, resulting in significant economic losses worldwide. A compelling impact of PRRSV infection is severe pneumonia. In the present study, we found that interleukin-17 (IL-17) was upregulated by PRRSV infection. Subsequently, we demonstrated that PI3K and p38MAPK signaling pathways were essential for PRRSV-induced IL-17 production as addition of phosphatidylinositol 3-kinase (PI3K) and p38MAPK inhibitors dramatically reduced IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…There are several reports documenting an increased population of IL-17A producing T cells and secretion of IL-17A in pigs, such as the presence of Actinobacillus pleuropneumoniae specific Th17 cells [CD4 + CD8α dim IL-17A + ] in the blood and lungs of porcine contagious pleuropneumonia infected pigs ( 39 ). IL-17 is a proinflammatory cytokine, likely associated with inflammation in the lungs of pigs infected with Porcine Reproductive and Respiratory Syndrome Virus (PRRSV), because in the serum and BAL fluid of highly pathogenic PRRSV infected pigs IL-17A was detected, and in PRRSV infected alveolar macrophages in vitro high levels of IL-17A gene expression was observed ( 40 ). The presence of enhanced IL-17A producing cells in PBMCs was detected following PMA and ionomycin activation in vitro ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports documenting an increased population of IL-17A producing T cells and secretion of IL-17A in pigs, such as the presence of Actinobacillus pleuropneumoniae specific Th17 cells [CD4 + CD8α dim IL-17A + ] in the blood and lungs of porcine contagious pleuropneumonia infected pigs ( 39 ). IL-17 is a proinflammatory cytokine, likely associated with inflammation in the lungs of pigs infected with Porcine Reproductive and Respiratory Syndrome Virus (PRRSV), because in the serum and BAL fluid of highly pathogenic PRRSV infected pigs IL-17A was detected, and in PRRSV infected alveolar macrophages in vitro high levels of IL-17A gene expression was observed ( 40 ). The presence of enhanced IL-17A producing cells in PBMCs was detected following PMA and ionomycin activation in vitro ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, nsp1 can increase the level of IL-10 as an inducer in vivo [ 35 ]. IL-17 is a proinflammatory cytokine associated with intense inflammation and is upregulated by HP-PRRSV of genotype 2 infection [ 13 , 37 ]. A study found that HP-PRRSV nsp11 could induce IL-17 production depending on the phosphatidylinositol 3-kinase (PI3K)-p38MAPK-C/EBPβ/CREB pathways [ 37 ].…”
Section: The Prrsv–host Interactionsmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome (PRRS) is one of the most severe swine diseases, characterized by reproductive failure in sows and respiratory disease in pigs of all ages [ 1 , 2 ]. The pathogenic agent is porcine reproductive and respiratory syndrome virus (PRRSV), which is an enveloped, positive-strand RNA virus of the family Arteriviridae [ 3 ]. PRRSV infection is highly restricted to cells in the monocyte/macrophage lineage such as porcine alveolar macrophages (PAMs), which are the primary targets of PRRSV in vivo [ 4 ].…”
Section: Introductionmentioning
confidence: 99%